(untitled) (Research, Society and Development, 2022)
The present research aims to carry out an individualized analysis of the relationship between stress in military police work with the development and worsening of Bruxism in public security professionals, analyzing and evaluating how police activities can infer the development of this pathology. The study, therefore, is qualitative research with an exploratory descriptive character of literature review in the category of narrative review, with literature review. Therefore, only articles containing the words: bruxism and stress or bruxism and military police were selected. At the end of the research, it was found that professionals in the Public Security area are daily exposed to extreme situations, which subject them to great dangers and risks and, consequently, to physical and mental exhaustion, which has generated physiological changes. As a result of professional circumstances, many state military personnel often complain and report having signs and symptoms of bruxism, making psychological care and follow-up by other specialists in TMD/Bruxism essential so that they do not get sick and become useless for this noble profession. of Military Police that they chose for their lives.